Complexes trans-Pt(BODIPY)X(PEt3)2: excitation energy-dependent fluorescence and phosphorescence emissions, oxygen sensing and photocatalysis. Issue 25 (3rd June 2016) - Irmler, Peter; Winter, Rainer F.
Abstract : Complexes trans -Pt(BODIPY)X(PEt3 )2 exhibit dual fluorescence and phosphorescence emissions, whose intensities are modulated by the anionic ligand X − and the excitation wavelengths. They constitute efficient single-component 3 O2 sensors and photocatalysts for aereal photooxidations with quantum yields near unity. Abstract : We report on five new complexes with the general formula trans -Pt(BODIPY)X(PEt3 )2 (Pt–X ), where the platinum(ii ) ion is σ-bonded to a 4, 4-difluoro-4-bora-3a, 4a-diaza- s -indacen-8-yl (BODIPY) and an anionic ligand X − (X − = Cl −, I −, NO2 −, NCS −, CH3 − ). All five complexes were characterized by multinuclear NMR, electronic absorption and luminescence spectroscopy and by X-ray diffraction analysis. Four of these complexes show efficient intersystem crossing (ISC) from an excited singlet state to a BODIPY-centred T1 state and exhibit dual fluorescence and phosphorescence emission from the BODIPY ligand. InPt–I, the fluorescence is almost completely quenched, whereas the phosphorescence quantum yield reaches a value of 40%. The rate of ISC and the ratio of phosphorescence to fluorescence emissions depend on the excitation wavelength ( i.e. on which specific transition is excited). The performance of these complexes as one-component oxygen sensors and their photocatalytic activities were tested by Stern–Volmer quenching experiments and by monitoring the oxidation of 1, 5-dihydroxynaphthalene with 1 O2 generated from the long-lived triplet state of the sensitizer by triplet–triplet annihilation with 3 O2 . Exceptionally high 1 O2 generation quantum yields of up to near unity were obtained.